1967
DOI: 10.1007/bf02666786
|View full text |Cite
|
Sign up to set email alerts
|

Oil composition ofCucurbita

Abstract: The entire range of fatty acid composition is found for seeds of self‐pollinated fruit from 22 individual plants representing 17 named species ofCucurbita. It appears that some varieties merit interest as a source of drying oil and edible oils. Xerophytes that are genetically related have similar types of unsaturation and molecular‐weight distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
2

Year Published

1987
1987
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 2 publications
1
9
0
2
Order By: Relevance
“…The mean seed oil content values reported here are similar to those reported by Bemis et al (1967) who noted an average of 33.5% oil in the (apparently entire) seed of C. moschata (cv. Butternut), 31.2% in the seed of cv.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The mean seed oil content values reported here are similar to those reported by Bemis et al (1967) who noted an average of 33.5% oil in the (apparently entire) seed of C. moschata (cv. Butternut), 31.2% in the seed of cv.…”
Section: Discussionsupporting
confidence: 91%
“…Bemis et al (1967) reported a fatty acid profile in the seed of C. mixta cv. Bemis et al (1967) reported a fatty acid profile in the seed of C. mixta cv.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The nutritional and oil characteristics of several other seeds of the Cucurbitaceae family have been studied in detail (Bemis et al ., 1968; Kamel et al ., 1982; Teotia & Ramakrishna, 1984; Bringi, 1987). It has been reported that the fatty acid composition of individual oil is species dependent and that the seeds of pumpkin and watermelon can be utilized successfully as sources of good quality edible oil and protein for human consumption (Chowdhury et al ., 1955; Sawaya et al ., 1983; Kamel et al ., 1985; Lazos, 1986; Akoh & Nwosu, 1992).…”
Section: Introductionmentioning
confidence: 99%